The Development of Content-Based English Material for Office Administration Program in Vocational High School - Rizal, Muhammad Sulton (RETAIN, 2021)
The teaching of English in Vocational High School is supposed to use English for Specific Purposes. It used specific materials in the process of teaching. However, not all English teachers of Vocational High School in Sidoarjo are responsive in using specific materials during the teaching and learning process. This study aims to identify the contents that should be included in the English materials for the Office Administration Program based on the result of need analysis, to develop appropriate English material for the Office Administration Program and to find out the teacher’s responses toward the English materials. This study used Educational Research and Development method in which the participants were 36 students of the Eleventh Grade and the English teacher of Office Administration Program. The data were collected through questionnaire, interview, and material adaptation instrument. The data were analyzed qualitatively by following stages, (a) organizing and familiarizing; (b) coding and reducing; and (c) interpreting and representing. The results of this study showed that the students of the office administration program need materials that contain specific contents related to their expertise such as secretary, public relation, customer service, and more like that. They agreed that the developed materials should include specific contents such as speaking skill, conversations related to the jobs in office administration, and office administration terms. In the process of developing material, the researcher applied the result of material adaptation and the syllabus designed by the researcher. Finally, the teacher stated that the material developed by the researcher is appropriately used in the teaching and learning process since the developed material can fulfil the students’ learning needs. She stated that the use of media such as illustration, audio listening, and video can help students achieve their goals in learning English. Keywords: Material development, English for Specific Purposes, Office Administration Program